Talent training practices in SME hotels - Ehsan Taghi Zadeh Ansari (Journal of Industrial Engineering and Management, 2024)
Purpose: This study aims to explore and analyse the intricacies of talent management and employee development practices within the hospitality industry. By delving into various training methodologies and assessing their impact, the study seeks to unveil the strengths, challenges, and opportunities each presents.